Peningkatan Kualitas Kerja Pegawai Melalui Budaya Organisasi Di Lingkungan Universitas Pembangunan Pancabudi Medan - Hasrul Azwar Hasibuan (CERED Indonesia Institute, 2022)
The purpose of implementing the activities of the Universitas Pembangunan Pancabudi Medan so far has been to implement an organizational culture in accordance with the university's vision and mission that can be implemented by seven basic values. The current conditions are still uneven socialization and employee understanding of the organizational culture that is applied. The results of the implementation of community service applied to employees of the Pancabudi Development University Medan show that the employees' understanding of organizational culture has been implemented which can improve the quality of their work by giving members an organizational identity, making the organization recognized as an innovative organization by developing new products. Organizational identity shows characteristics that distinguish it from other organizations that have different characteristics. Facilitating collective commitment, the organization is able to make its work proud to be a part of itself. Organizational members have a shared commitment to organizational norms that need to be followed and shared goals that need to be achieved.